Factors influencing adoption of mobile payment apps among generation z within Klang valley - Lau, Yan Yin (2022)
Due to Covid 19 pandemic, contactless contactless payments are now even more appreciated, especially in Asia Pacific region. Malaysia also facing the increasing mobile payment app usage trend among the Generation Z. Thus, this research intends to examine the effect of performance expectancy, effort expectancy, social influence, facilitating condition and convenience on the behavioural intention of Generation Z within Klang Valley. In this research, a quantitative approach was applied, with a sample size of 390 from Generation Z whom currently residing in Klang Valley. Furthermore, SPSS software was used to generate descriptive analysis, reliability test, Pearson Correlation Analysis and Multiple Regression Analysis.